Tackling the Future: Optimizing TVET Students of Employability Skills Through Self-Regulated Learning and Self-Efficacy - Lestari, Yeni Kusuma; Agung, Achmad Imam; Buditjahjanto, I Gusti Putu Asto; Anifah, Lilik; Wrahatnolo, Tri; Isnur, Subuh; Wanarti, Puput (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This article aims to dig deeper, analyzing the positive impact of applying Self-Regulated Learning (SRL) and Self-Efficacy (SE) on the development of students' employability skills in the vocational education environment. This research is quantitative research with a comparative causal approach; data collection was carried out with a survey approach through online forms on 202 students in vocational education expertise programs accounting and financial institutions (AFI), motorcycle engineering and business (MEB), automotive light vehicle engineering (ALVE), computer and network engineering (CNE) at four vocational schools in East Java. The research applies a closed questionnaire consisting of five options on the Likert scale. The respondents are voluntary and anonymous. The analysis testing is applied with SPSS analytical tool to answer the research hypothesis. The results showed that SRL and SE contribute simultaneously to shaping students' career readiness, with SRL influencing self-management and independent learning abilities. In contrast, SE motivates and strengthens confidence to apply these skills in the context of work.